POLICY EVALUATION PROPOSAL FOR “OPEN BUDGET” PARTICIPATORY BUDGET INITIATIVE IN UZBEKISTAN - Yusupov, Shokhjakhon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This evaluation proposal is drafted to examine the Open Budget initiative launched in 2021 to strengthen budgetary transparency, community engagement in decision-making, and improve government responsiveness. The program operates nationwide and allows eligible citizens to propose and vote for community development projects, which are then financed from local budget funds. The initiative and the Open Budget online portal are managed by the Ministry of Economy and Finance. The program is expanding quickly across regions, making a structured evaluation plan essential. The evaluation plan consists of implementation and outcome evaluation components, both of which apply mixed methods and primarily non-experimental and quasi-experimental designs. Implementation evaluation focuses on assessing whether the project runs smoothly in terms of proposal submission, project selection, voting, and financing of winning projects. Outcome evaluation assesses the broader impact of the initiative by examining institutional practices, citizens' trust and satisfaction, perceived transparency, and the alignment of winning projects with actual community needs. Evaluation methods include descriptive statistics, regression models, and qualitative analysis of focus group interviews.